Improving heavy metals removal, dewaterability and pathogen removal of waste activated sludge using enhanced chemical leaching. (20th October 2020) - Zhang, Liguo; Chen, Ying; Ma, Caixia; Liu, Lei; Pan, Jingshi; Li, Biqing; Wu, Xuewei; Wang, Qilin
Abstract: In order to enhance heavy metals removal, two enhanced chemical leaching techniques were examined comparatively using NaClO and NaNO2 with the addition of FeCl3 . The phosphorus release, dewaterability and pathogen removal of treated sludge were also examined after chemical leaching. The results showed that the heavy metals solubilization, improvement of dewaterability and pathogen removal were simultaneously achieved. Compared with NaClO treatment system, the better solubilization rates of Zn and Ni were observed in the NaNO2 treatment system. The improvement of Cu, Zn and Ni removal can be attributed to the disruption of the organically bound metal fraction based on metal distribution and EEM analysis. The TP loss caused by chemical leaching in this study was in the range of 47 %–54%. The treated sludge of the two systems could both meet Class A biosolids standards (US EPA) for land application. These results provided an alternative chemical leaching method for simultaneous improvement of sludge properties. Highlights: Better Zn and Ni solubilization observed in NaNO2 -enhanced chemical leaching. Improvements of Cu, Zn and Ni removal due to organically-bound metal release. Improvements of heavy metals solubilization, dewaterability and pathogen removal simultaneously achieved.